Speak More, Students! Harnessing Technology for Active Students' Engagement in EFL English-Speaking Classes - Lokollo, Natalia Christy Emy; Mali, Yustinus Calvin Gai (OKARA: Jurnal Bahasa dan Sastra, 2024)
One of the factors that causes EFL speaking challenges is students’ lack of engagement in their English-speaking classes. In that situation, technology might have the potential to help EFL teachers engage their students to speak more enthusiastically. This study explores technology tools used by teachers in EFL speaking, how they use the technology to teach EFL speaking to different levels of students, and to what extent the use of technology by the teachers can engage their students when learning EFL speaking. To achieve those research objectives, the researchers approached the study qualitatively by conducting a semi-structured interview with three EFL teachers from a non-formal school in Salatiga, Central Java, related to the purposes of the study. Through a rigorous peer debriefing process between the researchers, the data analysis results indicated that the participants used simple and common technology tools (e.g., PowerPoint, an online website, Google Docs, and Zoom) to teach EFL speaking. Notably, the technology tools could support the participants in engaging their students in the class by providing authentic and interesting materials that are completed with pictures and related to the students' lives. Questions for future research explorations are presented.